2013
DOI: 10.3354/aei00076
|View full text |Cite
|
Sign up to set email alerts
|

Wild fish aggregations around fish farms in the Gulf of Aqaba, Red Sea: implications for fisheries management and conservation

Abstract: Fish farm structures attract a variety of fish species by providing solid structure, and 'free meals' in the form of uneaten feed and feces that fall from the cages. In this study, we compared the composition and abundances of wild fish populations around 2 fish farms in the Red Sea and at nearby reference locations. Fish assemblages were evaluated by SCUBA divers carrying out rapid visual censuses in August, September and October 2007. A total of 87 238 fishes, representing 39 species and 25 families and a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…; Bacher et al . ; Özgül & Angel ). Using traditional tagging methods, Bjordal and Skar () found increased numbers of saithe over extended periods (months) around a fish farm in Norway.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bacher et al . ; Özgül & Angel ). Using traditional tagging methods, Bjordal and Skar () found increased numbers of saithe over extended periods (months) around a fish farm in Norway.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
“…() suggest that Atlantic bluefin tuna ( T. thynnus thynnus ) modify their migration patterns due to the attractiveness of a Mediterranean fish farm. Özgül and Angel () showed that the suite of species associated with Red Sea fish farms were usually associated with coral reefs, including those >4 km distant from cage sites, suggesting that the farms modified the distribution of these species. Anecdotal evidence from fishers in Norway suggests that migrating cod have changed their spawning migratory behaviour since the establishment of salmon farms in some areas.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 99%
“…In Galicia (Spain), Peteiro and Freire (2012) observed a number of different Sparidae fish species feeding on the macroalgae S. latissima and Undaria pinnatifida. This grazing problem is caused by the cages functioning as attractors for wild fish species (e.g., Dempster et al, 2002;Ozgul and Angel, 2013).…”
Section: Position Of Imta Componentsmentioning
confidence: 99%
“…However, the remarkable growth and extension of cage aquaculture facilities arise concerns in terms of environmental interactions, because marine cage farms attract wild fish populations due to eased foraging on the abundantly available pellets lost from net pens, and provide sheltering to hide from predator attacks in exposed marine conditions (Boyra, Sanchez‐Jerez, Tuya, Espino, & Haroun, ; Dempster, Sanchez‐Jerez, Bayle‐Sempere, GiménezCasalduero, & Valle, ; Dempster, Sanchez‐Jerez, Bayle‐Sempere, & Kingsford, ; Fernandez‐Jover, Sanchez‐Jerez, Bayle‐Sempere, Valle, & Dempster, ; Tuya, Boyra, Sanchez‐Jerez, & Haroun, ). Earlier studies reported aggregation of various wild fish stocks around fish pens in Spain (Dempster et al, ), in Australia (Dempster et al, ), the Canary Islands (Boyra et al, ; Tuya et al, ), in Turkey (Akyol & Ertosluk, ), in the Adriatic Sea (Bubic, Grubisic, Ticina, & Katavic, ), in the Red Sea (Golani, ; Özgül & Angel, ) and in Greece (Neofitou, ). However, to our knowledge so far, there is only one report regarding the aggregation of axillary seabream around cage farms in the Northern Aegean Sea which has been published by our team (Oztekin et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…. Earlier studies reported aggregation of various wild fish stocks around fish pens in Spain (Dempster et al, 2002), in Australia (Dempster et al, 2004), the Canary Islands (Boyra et al, 2004;Tuya et al, 2005), in Turkey (Akyol & Ertosluk, 2010), in the Adriatic Sea (Bubic, Grubisic, Ticina, & Katavic, 2011), in the Red Sea (Golani, 2003;Özgül & Angel, 2013) and in Greece (Neofitou, 2016). However, to our knowledge so far, there is only one report regarding the aggregation of axillary seabream around cage farms in the Northern Aegean Sea which has been published by our team (Oztekin et al, 2018).…”
mentioning
confidence: 99%